Let $A, B$ be two matrices such that $AB=A$ and $BA=B$, how do I show that $A\cdot A=A$ and $B\cdot B=B$?

Steps I took:

  1. Let $A= \left[\begin{array}{rr} a & b \\ c & d \\ \end{array}\right]$ and let $B= \left[\begin{array}{rr} w & x \\ y & z \\ \end{array}\right]$

  2. $\left[\begin{array}{rr} a & b \\ c & d \\ \end{array}\right] \cdot \left[\begin{array}{rr} w & x \\ y & z \\ \end{array}\right] = \left[\begin{array}{rr} aw+by & ax+bz \\ cw+dy & cx+dz \\ \end{array}\right] $ (Which is also equal to A)

  3. $\left[\begin{array}{rr} w & x \\ y & z \\ \end{array}\right] \cdot \left[\begin{array}{rr} a & b \\ c & d \\ \end{array}\right] = \left[\begin{array}{rr} wa+xc & wb+xd \\ ya+zc & yb+zd \\ \end{array}\right] $ (Which is also equal to B)

At this point I am stuck. I don't know how to proceed and I imagine that I started off on the wrong track to begin with. I'd like a hint to guide me in the right direction.

My proof after consultation with answerers below:


1) Since $AB=A$, we can say that: $(AB)A=AA$ which is equal to $A^2$

2) Then, (by associativity of matrix multiplication), we can say that $A(BA) = AB$ (since $BA=B$)

3) Then, $AB=A$ (since $AB=A$ was given)

4) Therefore, $AA$ is equal to $A$

5) Since $BA=B$, we can also say that: $(BA)B=BB$ which is equal to $B^2$

6) Then, (by associativity of matrix multiplication) we can say that $B(AB)=BA$ (since $AB=A$)

7) Then, $BA=B$

8) Therefore, $BB$ is equal to $B$

9) Thus, $AA$ is equal to $A$ and $BB$ is equal to $B$


  • $\begingroup$ Are you assuming they're $2 \times 2$ matrices? $\endgroup$ – Marcus M Nov 8 '15 at 16:52
  • $\begingroup$ @MarcusM Yes, I am. Is that wrong? $\endgroup$ – Cherry_Developer Nov 8 '15 at 16:53
  • 1
    $\begingroup$ @Cherry_Developer Well, it is not sufficient to look at the case of $2\times 2$ matrices if you want to prove something for general matrices. If you want to prove a statement of $2\times 2$ matrices, then it is not wrong. $\endgroup$ – Eff Nov 8 '15 at 16:54
  • 6
    $\begingroup$ This is not a good way to solve the exercise. The only thing you need is associativity of matrix product. $\endgroup$ – Crostul Nov 8 '15 at 16:58
  • $\begingroup$ One comment on the edit: associativity allows us to say $A(B)A = A(BA)$ or $(BA)B = B(AB)$. It is transitivity of equality that then allows us to say $AA = (AB)A = A(BA) = AB = A$, or $BB = B(AB) = B(AB) = BA = B$. So you're "combining steps" at step 2) and 6), $\endgroup$ – David Wheeler Nov 9 '15 at 23:50

If $AB = A$, and $BA = B$, then:

$A^2 = AA = (AB)A$ (since we can replace $A$ with $AB$ since they are equal)

$= A(BA)$ (by associativity of matrix multiplication)

$ = AB$ (since $BA = B$)

$= A$ (since $AB = A$).

Now you can try to use the same reasoning to prove $B^2 = B$.

This works for any two $n \times n$ matrices, $A,B$ that satisfy $AB = A$ and $BA = B$, not just $2 \times 2$ matrices.

  • $\begingroup$ I wrote up the proof. Would you be willing to look it over for me? $\endgroup$ – Cherry_Developer Nov 8 '15 at 21:10
  • $\begingroup$ @Cherry_Developer you are always welcome to post your own answer to a question here, even when it's your question. This happens a lot, actually. $\endgroup$ – David Wheeler Nov 9 '15 at 11:43
  • $\begingroup$ Would you be willing to look it over though? $\endgroup$ – Cherry_Developer Nov 9 '15 at 11:58
  • $\begingroup$ Sure, i don't see why not. $\endgroup$ – David Wheeler Nov 9 '15 at 12:07
  • $\begingroup$ I added it to my original post. Please look it over, if you can. Let me know what you think. $\endgroup$ – Cherry_Developer Nov 9 '15 at 12:40

Notice that $AA = (AB)(AB) = A(BA)B = ABB = AB = A$.

  • 2
    $\begingroup$ As noted in the comments above, associativity of the matrix product is crucial. From my vantage point, I immediately see the truth, here, but a beginner might not understand why we can play fast and loose with the parentheses. $\endgroup$ – David Wheeler Nov 8 '15 at 17:53

Hint: Start with $AA = (AB)A$ (because of the first equality)


$$A \cdot B = A \\ \implies (A \cdot B) \cdot A = A \cdot A \\ \implies A \cdot (B \cdot A) = A^2 \\ \implies A \cdot B = A^2 = A$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.